Ambiguities in english language teaching: designing english for specific purposes courses for a discipline-specific context - Azwani Mohamed, Mimi Nahariah (UTM Press., 2017)
The need for English language teaching to address specific language needs for a discipline has instigated growing demands for English for Specific Purposes (ESP) courses in higher education institutions in Malaysia. In the context of a university which focuses on engineering programmes, monitored by an engineering professional body, ESP courses designed and developed for higher education are expected to include learning outcomes which reflect integration between English language and engineering fields. In other words, these English language courses need to address the language needs in the engineering field. Thus, English language educators within this context need to have relevant knowledge and skills to enable them to design and develop appropriate ESP courses. Questions arise in relation to how English language courses developed have addressed this expectation. This paper examines the extent to which this expectation is translated into the ESP courses at one technical university in Malaysia. The findings showcase how this expectation is disseminated to the English language educators. This paper provides insight into the complex process of designing English language courses that could address the language needs of the engineering field. In addition, this paper highlights aspects to consider when designing an ESP course for a specific discipline.